Propriedades eletrônicas de nanobastões baseados em semicondutores de calcogenetos de metais de transição - Rodrigues, Ronaldo Adriano do Nascimento (2024)
Semiconductor systems with one or more reduced dimensions, where quantum confinement effects constrain the movement of electrons and holes, have been at the forefront of solid-state physics research for many years, drawing continuous interest from industry due to their potential for significant technological applications. In particular, nanorods (NR) are quantum systems in which charge carriers are completely restricted in all directions (zero degrees of freedom) and are confined in three dimensions. These materials are grown in elongated cylindrical geometries, resembling cigars or rods, with dimensions on the nanometer scale. The finite size of nanorods induces quantum confinement effects that significantly affect their energy level structure. Their optical, electrical, and mechanical properties are quasi-particles such as excitons, electrons, holes, and phonons confined in a cylinder with length L and radius r. In this work, we investigate the electronic states of electrons and holes in CdSe and CdTe nanorods in simple and core-shell configurations. The theoretical model for the simple configuration is based on the exact solution of the time-independent Schrödinger equation in cylindrical coordinates using the effective mass approximation. For the core-shell configurations, the effects of an external field on the electronic properties of the systems are also analyzed, employing numerical models based on the finite difference method.